A Review on Sickle Cells Disease - Al-Fatlawi, Abeer Cheaid Yousif (Scientific Journal of Medical Research, 2019)
Sickle cells disease (SCD) is homozygous inherited disorder lead to form hemoglobin called HbS with genotype (HbSS) when each parents carried this type of disorder gene. In which caused by point mutation in the gene that form ?-globin chain found on the short arm of chromosome 11 by replacement amino acid glutamine by valine at 6 position. This disorder can be affects millions peoples in the world and showed severe complications due to hemolysis RBCs and vaso-occlusive phenomenon. Low oxygen condition causes accelerated hemoglobin polymerization and form sickle shape of RBC then damage to it cell membrane and decreases elasticity. Many symptoms of SCD due to chronic hemolytic anemia such as episodes of painful crisis, stroke, acute chest syndrome and infection. In recent year’s best care of sickle cells disease patients like blood transfusion, bone marrow transplantation, Hydroxyurea and immunization to modifies pathogenesis by reduced mortality and morbidity with increased life of affected individuals.